COVID-19–Associated cardiac pathology at the postmortem evaluation: a collaborative systematic review. (August 2022) - Almamlouk, Raghed; Kashour, Tarek; Obeidat, Sawsan; Bois, Melanie C.; Maleszewski, Joseph J.; Omrani, Osama A.; Tleyjeh, Rana; Berbari, Elie; Chakhachiro, Zaher; Zein-Sabatto, Bassel; Gerberi, Dana; Tleyjeh, Imad M.; et al.
Abstract: Background: Many postmortem studies address the cardiovascular effects of COVID-19 and provide valuable information, but are limited by their small sample size. Objectives: The aim of this systematic review is to better understand the various aspects of the cardiovascular complications of COVID-19 by pooling data from a large number of autopsy studies. Data sources: We searched the online databases Ovid EBM Reviews, Ovid Embase, Ovid Medline, Scopus, and Web of Science for concepts of autopsy or histopathology combined with COVID-19, published between database inception and February 2021. We also searched for unpublished manuscripts using the medRxiv services operated by Cold Spring Harbor Laboratory. Study eligibility criteria: Articles were considered eligible for inclusion if they reported human postmortem cardiovascular findings among individuals with a confirmed SARS coronavirus type 2 (CoV-2) infection. Participants: Confirmed COVID-19 patients with post-mortem cardiovascular findings. Interventions: None. Methods: Studies were individually assessed for risk of selection, detection, and reporting biases. The median prevalence of different autopsy findings with associated interquartile ranges (IQRs). Results: This review cohort contained 50 studies including 548 hearts. The median age of the deceased was 69 years. The most prevalent acute cardiovascular findings were myocardial necrosis (median: 100.0%; IQR, 20%–100%; number of studies = 9; number of patients = 64) and myocardial oedema (median: 55.5%; IQR, 19.5%–92.5%; number of studies = 4; number of patients = 46). The median reported prevalence of extensive, focal active, and multifocal myocarditis were all 0.0%. The most prevalent chronic changes were myocyte hypertrophy (median: 69.0%; IQR, 46.8%–92.1%) and fibrosis (median: 35.0%; IQR, 35.0%–90.5%). SARS-CoV-2 was detected in the myocardium with median prevalence of 60.8% (IQR 40.4-95.6%). Conclusions: Our systematic review confirmed the high prevalence of acute and chronic cardiac pathologies in COVID-19 and SARS-CoV-2 cardiac tropism, as well as the low prevalence of myocarditis in COVID-19.